Perbandingan Kebijakan Pengendalian Deforestasi dan Penegakan Hukum di Indonesia dan Australia - Kisran Kisran; Ahmad Rustan; Rudi Iskandar Ichlas (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study comparatively analyzes deforestation control policies and law enforcement in Indonesia and Australia. The research uses normative juridical methods with legislative and comparative approaches, supported by secondary data on deforestation trends, regulatory instruments, and law enforcement practices in both countries. The analysis shows that Indonesia has a relatively comprehensive regulatory framework but faces serious obstacles at the level of implementation, including weak institutional coordination, inconsistent enforcement of sanctions, and the influence of economic interests in forest utilization. In contrast, Australia tends to rely on a combination of command-and-control instruments, market mechanisms, and a more stringent and transparent surveillance and sanctions system at the federal and state levels, thus providing a relatively stronger deterrent effect. This comparison reveals that differences in institutional design, quality of governance, and level of public participation contribute significantly to the effectiveness of deforestation control in each country. This article recommends strengthening cross-sectoral coordination, increasing the independence and capacity of law enforcement, and expanding public participation and oversight mechanisms as policy lessons that can be adapted to improve deforestation control in Indonesia